ISOLATION AND MORPHOLOGIC CARACTERIZATION OF STREPTOCOCCUS SP. STRAINS FROM HEALTHY HORSES. - Levek, Marcos Willian; Tasca, Caiane; Vargas, Agueda Castagna de; Baratto, César Milton (Anais eletrônicos do International Symposium on Science and Biotechnology, 2017)
Streptococcus strains are potential producers of hyaluronic acid, and they are present on the nasal cavity, being an etiologic agent of equine strangles. The objective of this work is the identification of b-hemolytic Streptococcus sp. strains isolated from horses. The collect of samples was made between August and October 2017 in properties from Santa Catarina. A questionnaire was carried out to determine the animal health profile. After being collected, the samples were seeded and cultured on 5% sheep blood agar during 48 hours at 37ºC and aerobic/anaerobic conditions. Catalase test and gram staining were carried out in the isolated colonies. During the above-mentioned period 13 samples were collected from healthy horses: 07 females and 06 males, all vaccinated against infectious disease and with strangles historic. None of the isolates obtained was characterized as b-hemolytic, 07 isolates were characterized as Streptococcus α-hemolytic and presented compatible morphology in gram staining. According to another study that isolated 38 samples, the majority of the samples was identified as the cause of equine adenitis. The results obtained from some authors shows the difficult to isolate Streptococcus strains from healthy horses. However, collecting sample from animals that learn the symptoms of strangles will facilitate the isolation of target microorganisms.